Emerging Asia's impact on food and oil prices: A model-based analysis - René Lalonde; Philipp Maier; Dirk Muir (Bank of Canada, 2009)
The authors explore the usefulness of macroeconomic models in analyzing global economic developments by examining movements in commodity prices between July 2007 and July 2008. They use the Bank of Canada's version of the Global Economy Model and investigate the longerterm outlook for commodity prices by constructing two different, globally consistent, scenarios for emerging Asia. In the first scenario, the authors assume that a persistent increase in emerging Asia's productivity underlies its sustained growth; in the second scenario, they assume that a combination of productivity increases and a temporary demand shock underlie its growth. The demand for commodities increases in both scenarios, but, by comparing the two, the authors reveal that each scenario has considerably different economic implications. Allowing for the possibility that a small share of emerging Asia's growth might be fuelled by a temporary demand shock generates a strong boom-bust outcome for emerging Asia, and amplifies the volatility in commodity markets. The authors also investigate the possibility that emerging markets react to inflation by revaluing their exchange rates by 10 per cent. This affects the outlook for commodities only marginally.
Keywords: E30; E50; E58; E60; 330; International topics; Recent economic and financial developments; Internationale Wirtschaftsbeziehungen; Wirtschaftswachstum; Preisniveau; Nahrungsmittel; Erdöl; Asien; Welt